Evaluation of a plastic composite produced with residues of sugarcane bagasse and polypropylene wihtout additives - Battistelle, Rosane Aparecida Gomes; Bezerra, Barbara Stolte [UNESP]; Valarelli, Ivaldo de Domenico; Branco, Luiz A. Melgaço N.; Chahud, Eduardo; Christoforo, André Luis (My University, 2015)
In this research the aim was produce and evaluate a plastic composite using recycled polypropylene (PP) and fibers from sugarcane bagasse residues (SC), without the use of additives. This analysis was based on laboratorial tests for physical and mechanical characterization, according to the standards ASTM D256-00, D638-101 and D570-98 were analyzed: water absorption, thickness swelling, impact resistance, tensile strength and its correspondent deformation. For comparison it was elaborated three different compositions: 100% PP; 80% PP+20%SC; 70%PP+30%SC. The results indicate a positive correlation with the content of fiber and water absorption and thickness swelling. In the tension tests, the composites with fibers increase the value of resistance for physical efforts, bringing advantages as durability and integrity of the material, showing a viability of the composites.
Keywords: Plastic composite; Polypropylene recycled; Sugarcane residues